The Effect Of Temulawak And Ginger Herbal Drinks On Reducing Menstrual Pain In Adolescent Girls At UPT Puskesmas Tirtayasa In 2024 - Haqqul Aqiqoh; Aprilya Nency; Ageng Septa Rini (Sean Institute, 2024)
Dysmenorrhea is a common physical disorder experienced by women during menstruation, characterized by pain or cramps in the lower abdomen that often radiate to the thighs and lower back. Approximately 50% of women worldwide experience dysmenorrhea, with a prevalence reaching 90% according to WHO data, where 11-15% suffer from severe dysmenorrhea. This study aims to examine the effect of consuming temulawak (Curcuma xanthorrhiza) and ginger herbal drinks on reducing menstrual pain in adolescent girls at UPT Puskesmas Tirtayasa, Serang-Banten, in 2024. The research employs a case study design, using primary data obtained through observation. The study compares the effects of temulawak herbal drink on reducing menstrual pain in adolescent girls with those given ginger herbal drink. The sample consists of two adolescent girls experiencing menstruation and menstrual pain. Interventions were conducted by comparing the administration of temulawak and ginger herbal drinks as non-pharmacological therapies. Data were collected using observation sheets and analyzed descriptively. The findings, gathered through observation sheets, indicate that non-pharmacological therapy in the form of consuming ginger and temulawak herbal drinks, combined with interventions using both types of herbal drinks, effectively reduces the intensity of menstrual pain in adolescent girls. Those who consumed a combination of ginger and temulawak herbal drinks experienced a significant reduction in the intensity of menstrual pain.